(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Global Buildings account for up to 40% of world energy consumption and 36% of carbon dioxide emissions. Consumption is anticipated to increase by up to 50% by the year 2030. The construction industry in India consumes 70% of all electricity generated in the country. According to studies, buildings utilize more than half of their energy for tenant comfort, such as cooling and lighting. Building energy consumption will continue to rise unless buildings can be built to create enough energy to meet the growing energy demand of these structures. A zero-energy building has zero net energy consumption, which indicates that the entire quantity of energy required by the structure over the course of a year is equal to the amount of energy produced on or off the site. These structures produce fewer greenhouse gases and have a lower impact on the environment. This research aims to review some material on zero-energy buildings in India and recommend solutions for tenants to reduce their energy consumption. A building with zero net energy usage is referred to as a zero-energy building (ZEB). In recent years, ZEBs have gotten a lot of attention in a lot of nations because they are seen as a key technique for achieving energy conservation and lowering greenhouse gas emissions. The concept of going to ZEB via law has sparked a lot of controversy in various nations about whether it is currently feasible. With special reference to Kashmir, the fundamental difficulties for establishing ZEB are examined from both an engineering and an architectural standpoint. Also being considered are the necessary arrangements that must be deployed in Net Zero Energy Buildings in the Kashmir division of the UT of Jammu & Kashmir, India, as well as other crucial issues.